Retribution - Hagberg, David (Hagberg, David. Kirk McGarvey adventures., 2015)
"On May 1, 2011, a team of twenty-four members of US SEAL Team Six swooped down on the compound of Osama bin Laden in Abbottabad, Pakistan. Their mission, code-named Neptune Spear, was to find and kill the terrorist leader. The mission was a success. Since that day, elements of the government of Pakistan have harbored a deep hatred for the SEALs who violated their sovereign territory. Now they've hired a team of German assassins to kill all twenty-four of the ST6 operators"--Amazon.com.